Effects of different treatments on purity of silica from soluble sodium silicate - Martines, MAU; Pecoraro, Édison [UNESP]; Simoneti, J. A.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. (Taylor & Francis Inc, 2000)
Noncrystalline silica was obtained with low iron, sodium, and nitrate ions concentrations from soluble sodium silicate (water glass) and nitric acid solution. Extractions with nitric acid solution and/or deionized water and/or dialysis were carried out to eliminate soluble metal ions. Products were dried in a microwave oven and characterized by chemical analysis, XRD, and IR. Dialysis seems to be the best treatment for the elimination of sodium and nitrate ions. Silica purified by nitric acid and water extractions followed by dialysis yields the purest silica sample.
Keywords: silica; soxhlet extraction; dialysis